2007
DOI: 10.1007/s00424-007-0318-z
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and chloride absorptive defects in the small intestine in Slc26a6 null mice

Abstract: PAT1 (Slc26a6) is located on the apical membrane of the small intestinal villi, but its role for salt absorption has not been studied. To ascertain the role of Slc26a6 in jejunal sodium and chloride absorption, and its interplay with NHE3, muscle-stripped jejuna from Slc26a6+/+ and -/- and NHE3 +/+ and -/- mice were mounted in Ussing chambers and electrical parameters, and (36)Cl(-) and (22)Na(+) fluxes were measured. In parallel studies, expression of the apical Na(+)/H(+) exchanger (NHE3) was examined by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 46 publications
6
52
0
Order By: Relevance
“…and NHE3 interact (42), supporting the observed defects in Na ϩ and Cl Ϫ absorption in the small intestine of SLC26A6-null mice (45).…”
Section: Disproportionately Robust Secretagogue-induced Membrane Recrsupporting
confidence: 63%
“…and NHE3 interact (42), supporting the observed defects in Na ϩ and Cl Ϫ absorption in the small intestine of SLC26A6-null mice (45).…”
Section: Disproportionately Robust Secretagogue-induced Membrane Recrsupporting
confidence: 63%
“…As previously mentioned, activity of the apical Na + /H + exchanger maintains the H + electrochemical gradient necessary for the correct functionality of PAT1 (Anderson et al 2004, Seidler et al 2008. Moreover, it has been demonstrated that activation of cAMP/PKA pathway decreases the activity of the Na + /H + exchanger NHE3 (Anderson & Thwaites 2005) and indirectly inhibits PAT1, in line with the fact that PAT1 has no intracellular PKA phosphorylation sites (Chen et al 2004).…”
Section: Discussionmentioning
confidence: 75%
“…Slc26a6 -/-mice show impaired intestinal and pancreatic duct Clabsorption and HCO 3 -secretion (42,99,123), along with impaired pancreatic fluid secretion (123). Moreover, deletion of Slc26a6 in the pancreatic duct results in disregulation of CFTR (123), indicating a role of Slc26a6 in the overall epithelial fluid and electrolyte secretion.…”
Section: Groupmentioning
confidence: 99%